Application of DSTATCOM for Surplus Power Circulation in MV and LV Distribution Networks with Single–phase Distributed Energy Resources - Shahnia, Farhad; Chandrasena, Ruwan Pathiranage Sarath; Ghosh, Arindam; Rajakaruna, Sumedha (Institute of Electrical and Electronics Engineers (IEEE), 2014)
Presence of large number of single–phase distributed energy resources (DER) in a particular phase can cause reverse power flow in that phase making the upstream network unbalanced. In this paper, the possibility of using a Distribution Static Compensator (DSTATCOM) is explored to circulate the excess generation in one phase to the phases with higher load demand. Two different topologies are proposed for DSTATCOM to be installed in low and medium voltage feeders. Similarly, two different power circulation strategies are proposed for power circulation through the DSTATCOM. A suitable switching feedback control scheme is developed and utilized for each topology. In addition to power circulation, the DSTATCOM facilitates a set of balanced phase power flow from the upstream side. The proposals are validated via PSCAD/EMTDC simulation studies.